2006
DOI: 10.1016/j.foreco.2006.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Growth and species interactions of Eucalyptus pellita in a mixed and monoculture plantation in the humid tropics of north Queensland

Abstract: This study investigated whether mixed-species designs can increase the growth of a tropical eucalypt when compared to monocultures. Monocultures of Eucalyptus pellita (E) and Acacia peregrina (A) and mixtures in various proportions (75E:25A, 50E:50A, 25E:75A) were planted in a replacement series design on the Atherton Tablelands of north Queensland, Australia. High mortality in the establishment phase due to repeated damage by tropical cyclones altered the trial design. Effects of experimental designs on tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 24 publications
0
60
0
Order By: Relevance
“…Differences in species' competitiveness are, however, not accounted for by HCI. Nevertheless, this index has proven useful as a measure of the competitive effects of neighboring trees on individual tree growth (Clinton et al 1997, Bristow et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in species' competitiveness are, however, not accounted for by HCI. Nevertheless, this index has proven useful as a measure of the competitive effects of neighboring trees on individual tree growth (Clinton et al 1997, Bristow et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced productivity in mixtures has often been associated with asymmetric competition between species as plantations develop (Cavard et al 2010;Hunt et al 2006;Chen et al 2003). Whilst studies investigating neighbourhood effects have identified the inter-specific competitive effects in mixtures (Canham et al 2004;Bristow et al 2006), others have found the size of neighbours, rather than species identity, as the largest source of variation in individual tree diameter and height (Erickson et al 2009;Potvin and Dutilleul 2009).…”
mentioning
confidence: 99%
“…One should not conclude from Table 1 that Acacia mangium is the ideal species, as the table shows only those species planted in more than one rainfall-soil category. Eucalyptus pellita was also widely planted, and performed well, particularly when planted in a mixture with acacias (Bristow et al 2006). Glencross and Nichols (2005) presented similar data for plantings in northern New South Wales, and ranked species according to height, diameter and stem straightness.…”
Section: Plantation Management and Growthmentioning
confidence: 90%